PEMETAAN BIBLIOMETRIK TERHADAP TREN RISET MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT - Ray Leonard Januar; Ishaq Nuriadin (STKIP Andi Matappa, 2023)
The purpose of this study was to look at research trends and the distribution of research on the Missouri Mathematics Project learning model. The research method used is a bibliometric analysis method using the Publish or Perish and Vos Viewer applications. The number of publications on the Missouri Mathematics Project Learning Model was 177 articles from 2012 – 2022. There was a constant number of publications between 2014 – 2017 and a significant increase in 2018. Then the number of publications decreased in 2021 and 2022. Visualization results from the application Vos Viewer shows there are two clusters and each cluster has four variables each. The dominant variable is the Missouri Mathematics Project variable. This indicates that the Missouri Mathematics Project learning model has been extensively researched. Variables that are rarely researched are variables about effectiveness and study. For the next researcher, you can include the effectiveness or study variable as a research variable.